Electrodeposition and Low-Temperature Post-Treatment of Nanocrystalline SnO2 Films for Flexible Dye-Sensitized Solar Cells. (7th March 2012) - Li, Shengjun; Li, Yongjun; Chen, Zeng; Liu, Junhui; Zhang, Weifeng
Abstract : SnO 2 porous films were electrodeposited on Ti substrate using pulse-potential technique. These deposited films were dealt with different post-treatments. The effects of the post treatments were investigated through X-ray diffraction, FE-SEM, and Raman spectra. These investigations showed that crystal nanoporous SnO 2 films were obtained through low-temperature post-treatment process. The photoelectric conversion efficiency of the SnO 2 film treated with both the water vapour treatment and ultraviolet illumination was improved to be 0.35% which was comparable with the conversion efficiency of the film sintered at 550 ∘ C .